Value of Echocardiography in the Treatment of Patients With Acute Heart Failure - Izumo, Masaki (Frontiers in Cardiovascular Medicine, 2021)
Heart failure (HF) is a burden in pandemic medicine resulting in high mortality and morbidity . Because acute HF is a life-threatening event, its diagnosis and choice of optimal treatment are important to improve outcomes. Furthermore, understanding the cause and hemodynamics of acute HF is important in selecting the optimal treatment for these patients. Echocardiography is widely used in daily clinical practice because of its noninvasive nature and excellent portability to understand cardiac function and hemodynamics. Echocardiography is highly recommended by guidelines in the practice of HF, but evidence is limited. In this review, I would like to share clinical value of echocardiography in the treatment of patients with acute HF and discuss the usefulness of echocardiography.